The relationship between emotion regulation strategies and job search behavior among fourth‐year university students. (23rd June 2017) - Wang, Ling; Xu, Huihui; Zhang, Xue; Fang, Ping
ABSTRACT: The job search process is a stressful experience. This study investigated the effect of emotion regulation strategies on job search behavior in combination with anxiety and job search self‐efficacy among Chinese university fourth‐year students ( N = 816, mean age = 21.98, 31.5% male, 34.9% majored in science, 18.0% from "211 Project" universities). Results showed that cognitive reappraisal was positively related to job search behavior, while expressive suppression was negatively related to job search behavior. Additionally, anxiety was negatively related to job search behavior, while job search self‐efficacy was positively associated with job search behavior. Moreover, both anxiety and job search self‐efficacy mediated the relationship between emotion regulation strategies and job search behavior. In general, emotion regulation strategies played an important role in job search behavior. Implications include the notion that emotion regulation interventions may be helpful to increase job search behavior among university students.